Retroflexion in Nepali - Khatiwada, Rajesh (Gipan, 2019)
Nepali, an Indo-Aryan language spoken in Nepal along with India and Bhutan, and some parts of Burma, possesses three coronal stops (2 plosives and 1 affricate). Retroflexion is traditionally considered as the distinctive feature between two different types of plosives. Though retroflexion in Nepali is considered- like in the case of other Indo-Aryan languages- a fundamental distinctive articulatory parameter (Bhat 1973, Ladefoged and Bhaskararao 1983, Ladefoged and Maddieson 1996), Pokharel (1989), however, claims that there is no retroflex category in Nepali, because the “so-called” (sic.) Nepali retroflex stops are not produced with the “tongue tip curling back” as it is described in the traditional grammar. In this work, I have tried to show that this claim is just one side of the story and that the “retroflex” as a phonetic and phonological category “does exist” in Nepali. Based on two different palatographic and linguographic studies (of 9 speakers – four females and five males- of Nepal) I have presented a different scenario than that of Pokharel, without completely denying his claim.